2023
DOI: 10.1007/s10919-022-00421-6
|View full text |Cite|
|
Sign up to set email alerts
|

Emoji Alter the Perception of Emotion in Affectively Neutral Text messages

Abstract: Previous studies of emoji effects on text sentiment demonstrate mixed findings. Further, these studies are limited by confounds, e.g., underlying text sentiment, lack of ecological validity. We considered emoji effects on the emotional valence of affectively neutral English-language text messages. We additionally considered differences across US-American, British, and Danish participants. 217 participants considered screenshots of question-and-response text message exchanges with/without emoji, in a 4 (emoji t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Existing studies on emoji usage behavior, one is to explore the emoji usage behavior itself in order to gain insight into its behavioral patterns and communication trends; the other is to explore the user's preferences and attitudes, as well as the communication effects of emoji in social interaction by analyzing emoji usage behavior. Emojis can help users express emotions during the communication process (Wall et al, 2016), and emojis can change the perception of emotion in the original sentiment of a text message (Neel et al, 2023). It can also convey semantics (Na'aman et al, 2017), becoming an auxiliary language in the communication process.…”
Section: Influences On Emoji Use Behaviormentioning
confidence: 99%
“…Existing studies on emoji usage behavior, one is to explore the emoji usage behavior itself in order to gain insight into its behavioral patterns and communication trends; the other is to explore the user's preferences and attitudes, as well as the communication effects of emoji in social interaction by analyzing emoji usage behavior. Emojis can help users express emotions during the communication process (Wall et al, 2016), and emojis can change the perception of emotion in the original sentiment of a text message (Neel et al, 2023). It can also convey semantics (Na'aman et al, 2017), becoming an auxiliary language in the communication process.…”
Section: Influences On Emoji Use Behaviormentioning
confidence: 99%
“…They conducted two experiments. They found that texts paired with positive emoji were rated more positively than texts paired with negative emoji (as Boutet et al, 2021;Hand et al, 2022;Neel et al, 2023). Furthermore, texts paired with stronger-valenced emoji were rated as less neutral compared to texts paired with milder-valenced emoji.…”
Section: Editorial On the Research Topic Language And The Digital Fro...mentioning
confidence: 99%
“…Emojis have been observed to progressively replace the role of emoticons in computer-mediated communications [17]. Although emojis are often used and interpreted the same way emoticons are [18,19], neurological evidence suggests that emojis are more likely to be perceived as human faces than emoticons [20][21][22]. Therefore, in the current research, we use the term emojis.…”
Section: Emojis As Nonverbal Cuesmentioning
confidence: 99%